A binding site for the antibiotic GE81112 in the ribosomal mRNA channel - Andreas Schedlbauer (mBio, 2025)
ABSTRACT The initiation phase is the rate-limiting step of protein synthesis (translation) and is finely regulated, making it an important drug target. In bacteria, initiation is guided by three initiation factors and involves positioning the start site on the messenger RNA within the P-site on the small ribosomal subunit (30S), where it is decoded by the initiator fMet–tRNA. This process can be efficiently inhibited by GE81112, a natural hydrophilic, noncyclic, nonribosomal tetrapeptide. It is found in nature in three structural variants (A, B, and B1 with molecular masses of 643–658 Da). Previous biochemical and structural characterization of GE81112 indicates that the primary mechanism of action of this antibiotic is to (i) prevent the initiator fMet–tRNA from binding correctly to the P-site and (ii) block conformational rearrangements in initiation factor IF3, resulting in an unlocked 30S preIC state. In this study, using cryo-EM, we have determined the binding site of GE81112 in initiation complexes (3.2–3.7 Å) and on empty ribosomes (2.09 Å). This binding site is within the mRNA channel but remote from the binding site of the initiation factors and initiator fMet–tRNA. This suggests that it acts allosterically to prevent the initiator fMet–tRNA from being locked into place. The binding mode is consistent with previous biochemical studies and recent work identifying the key pharmacophores of GE81112.IMPORTANCEThis study uses high-resolution cryo-electron microscopy (cryo-EM) to reveal the precise binding site of the antibiotic GE81112 on the bacterial ribosome's 30S subunit. GE81112 targets the initiation phase of bacterial protein synthesis, specifically interacting within the mRNA channel, distant from the initiation factor and initiator tRNA-binding sites. This indicates that GE81112 acts allosterically, disrupting and preventing conformational rearrangements in IF3 and the proper positioning of the initiator tRNA, stalling the ribosome in an unlocked pre-initiation complex. The findings identify key ribosomal interactions, including conserved nucleotides in helices 23, 24, and 45, and protein S11, highlighting GE81112's unique binding mode among initiation inhibitors. This structural characterization enhances our understanding of antibiotic interference with translation initiation and provides insights to support rational design strategies for improved GE81112 derivatives.